Study on the Evolution Characteristics of Two-Zone Failure Mode of the Overburden Strata under Shallow Buried Thick Seam Mining. (7th April 2019) - Yang, Daming; Guo, Wenbing; Tan, Yi
Abstract : There are risks of water burst and sand inrush in the working face of the Northwest Mining Area in China. Based on the 22407 working face of Halagou coal mine, the evolution characteristics and mechanism of a two-zone failure mode of the overburden strata in shallow buried thick seam mining were thoroughly analysed using physical modelling, theoretical analysis, on-site observation, and other research methods. A method to calculate the overburden fissure width was also proposed. The analysis results indicated that the evolution of a two-zone failure mode of the overburden strata mainly includes four stages: gestation, formation, transformation, and stabilization. In the transformation stage, a fracture zone is transformed into a caving zone. The caving zone and fracture zone are separately transferred to the working face direction based on the structure type of key strata of voussoir beam and cantilever beam after the heights of the two zones stabilize, and the "two-belt" cracks are mainly composed of inclined and horizontal fissures. Based on this study, the mechanism of the two-zone failure mode of overburden strata development was analysed according to the mining height and overburden strata key layer structure. This paper serves as a guide for safe and green mining on shallow buried thick seams.